Playful strategy applied to teaching and learning analytical chemistry - Martins , Vitória Caroline de Souza; Silva, Bianca Souza da; Negrão, Charles Alberto Brito; Lima, João Pedro dos Reis; Silva, Thiago de Melo e; Araújo, Yasmin Ribeiro e Silva; Souza, Silvia Helena da Silva e; Souza, Ewerton Carvalho de; Pantoja, Samantha Siqueira; Silva, Antonio dos Santos (Seven Editora, 2024)
Mediated learning is a teaching model in which a mediator stands between the learner and the world of stimuli, facilitating interpretation and understanding. This model has numerous modes of application, one of which is playful activity, or didactic games. This work presents the proposal to develop a didactic game, entitled "Analytical Chemistry Target Shooting", as an auxiliary tool in the teaching and learning process of analytical chemistry in higher education courses, especially for introductory subjects. For its construction, low-cost and easily accessible materials were used, aiming for a better applicability of the method, with the game consisting of a pair of darts, a target, a set of question cards of three levels of difficulty, a board and markers of the players. Therefore, a board game was obtained that leads to the fixation of the content taught in the classroom, in a relaxed and cheerful way, contributing to making chemistry teaching less complicated, tedious and aversive to the student, who becomes a more active in their learning. DOI:https://doi.org/10.56238/sevened2024.009-012